HARDWARE AND SOFTWARE COMPLEX FOR FRICTION AND WEAR INVESTIGATIONS BY THE «DISC ON PLATE» METHOD - F. F. Komarov; V. V. Pilko; V. N. Kuleshov (Приборы и методы измерений, 2016)
Transition of the precision engineering and instrumentation to the widespread use of nanoscale structures and thin layers requires improved localization methods for measuring the depth of the material. Unified standards and the generally accepted methods for measuring the wear resistance and friction coefficient are not currently available. The aim of this work was the development of a universal friction machine with the simplified requirements for the preparation and the geometric shape of the sample and the opposing disc. An important requirement for the equipment and the method of measurement is the ability to measure the friction coefficient and the determination of the wear resistance of coatings and hardened layers of micron and submicron thicknesses. Another important requirement is modeling in the experiment of acyclic friction process, as close as possible to the real operating conditions of components and parts. Both of these conditions are successfully realized by using the method of «disc on plate». Implementation of «disk on plate» method was used to simplify and improve the rapid measurement, and to minimize load on the friction assembly, reduce friction pair temperature, increase the sensitivity and improve the resistive bridge thermal stabilization. The complex for the study of friction and wear processes of various materials pairs in conditions close to operational was manufactured and tested. The measuring console with a low value of the parasitic load on the measuring cell was designed. A computerized hardware and software system for the registration of the friction parameters of the process was developed. The software for processing and storage of experiment results was developed. The software is compatible with modern Windows operating systems. The file format for measurement results storage is compatible with the conventional graphic editors and could be processed by means of Exсel. The main principles of the analysis and processing of the results are consequentially described. Typical results of usage of the developed machine for friction coefficient measurements and the determination of the wear resistance of massive, homogeneous surfacehardened materials and alloys with coatings are shown. The high efficiency of the created equipment complex during investigation of coatings, optimization of coating depositing processes and the modification of the surface layers are shown in the study. The efficiency of the complex was confirmed by the study of the modified layers and micron thickness coatings. It was found that the friction coefficient and wear resistance of construction materials, modified thin microcrystalline layers and nanostructured coatings was effectively controlled by using of the created complex.